Peculiarities of the mathematical model and program of calculation of the continuous sorted rolling - S. M. Zhuchkov; L. V. Kulakov; K. Ju. Kluchnikov; A. P. Ivanov; V. A. Tishchenko (Литьë и металлургия, 2003)
There is developed the program of calculation of the endless sorted rolling parameters, which is easy adapted for analysis of rolling conditions at section mills of different types with different design-structured composition of the main technological equipment In the mathematical model of the process of the endless sorted rolling, put into basis of this program, there is taken into account more strongly the changing of the temperature field of breakdown bar along the length of the mill and its influence on changing of the stress liquidity in the mill cages and in its intercage spaces.